THE EFFECTIVENESS OF IMPLEMENTING THE STEAM APPROACH BASED ON PROJECT-BASED LEARNING (PJBL) ON MIDDLE SCHOOL STUDENTS' SELF-CONFIDENCE AND CREATIVITY: EFEKTIVITAS PENERAPAN PENDEKATAN STEAM BERBASIS PROJECT BASED LEARNING (PJBL) TERHADAP KEPERCAYAAN DIRI DAN KREATIVITAS SISWA SMP - Mansyur, Azizul Jabbar; Bahar, Afipa Amalia; Dasari, Dadan (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
This study aims to determine the self-confidence and creativity of Grade VIII students of SMP Negeri 33 Makassar and also to evaluate the effectiveness of implementing the STEAM approach based on Project Based Learning at SMP Negeri 33 Makassar. The research sample consisted of two classes which were then divided into a control class and an experimental class. The experimental class was given treatment in the form of applying the STEAM approach based on project-based Learning. The main instrument in this study was the researcher. The supporting instruments used were student response questionnaires, student self-confidence questionnaires, student activity observation sheets, and student creativity observation sheets. Then the data obtained is processed and interpreted. The results showed that: (1) The self-confidence of students who were taught using the STEAM approach based on Project Based Learning was better than those taught with conventional learning models. (2) the creativity of students taught with the STEAM approach based on Project Based Learning is better than those taught with conventional learning models. (3) The application of project-based Learning-based STEAM Approach is effectively applied in learning mathematics material in class VIII SMP Negeri 33 Makassar.